Pembelajaran Kecerdasan Jamak Pada Anak Usia Dini - Radjiman Ismail (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2016)
Growth and developments in pre school will determine the future of the child. Developments in the early period, intellectually, emotionally, as well as social must be designed optimally, especially in learning at school or at home. Physical growth should also be considered to provide a wide range of learning that can foster motor skills are fine and coarse.Growth and development of intelligence from an early age is a must, so that the various efforts in learning is essentially an effort to determine how big the potential of the students. By knowing the potential of students from an early age, will contribute to appropriate learning targets. That is, learning to develop all its potential, both interest talents and creativity. Thus the child can grow optimally.